Effects of stair‐climbing on balance, gait, strength, resting heart rate, and submaximal endurance in healthy seniors. Issue 2 (27th August 2013) - Donath, L.; Faude, O.; Roth, R.; Zahner, L.
<x xml:space="preserve">Abstract</x> Stair‐climbing serves as a feasible opportunity to remain physically active within everyday‐life. Data on neuromuscular and cardiorespiratory performance after regular stair‐climbing in seniors are scarce. Forty‐eight seniors were stratified to a one‐ (taking every step, INT1) or two‐step strategy (every second step, INT2) or a control group (CON). Thirty‐nine seniors [females: n = 22, males: n = 17; age: 70.5 (SD 5.1) years; BMI: 25.8 (3.1) kg/m2] completed the 8‐week intervention (three weekly sessions). Before and after the intervention, balance, gait, strength, and submaximal endurance (at different intensities) were assessed. Maximal strength and explosive power did not improve significantly (0.10 < P < 0.78). Resting heart rate was significantly reduced in INT2 (−8/min) compared with INT1 (0/min, P = 0.02) and CON (0/min, P = 0.03). Compared with CON, perceived exertion for all intensities (0.007 < P < 0.03) and submaximal exercise heart rate during moderate uphill walking significantly decreased (−11/min; P < 0.05) in INT2. Step counts for forward beam balancing (4.5 cm width) increased in INT2 (P = 0.007) compared with CON. With more pronounced effects in INT2, stair‐climbing significantly improved resting and exercise heart rates, perceived exertion, and dynamic balance performance in healthy seniors and may contribute to better overall fitness, reduced fall risk, and less perceived strain during daily life activities.